Marine Algal Antioxidants - Brunet, Christophe; Sansone, Clementina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book entitled Marine Algal Antioxidants, as a special issue of the Antioxidants journal, encloses eleven scientific articles with a preface written by the two editors, Christophe Brunet and Clementina Sansone. Marine Algal Antioxidants book reports advances of the research on marine photosynthetic organisms for the growth of biotechnological pipelines aimed to enhance antioxidant molecules production by algae. More than twenty scientists share the results of their research and highlight the relevance of algae for developing marine biotechnology products to flourish the requirements of nutraceuticals or cosmeceuticals in the defense of human health. Multidisciplinarity of the scientific approaches presented in this book - such as physiological, molecular, chemistry, technical or technological methodologies - lays the foundation for harmonizing the links between them towards the unique goal of the improvement of marine algal factory processes.